Pemberdayaan Perempuan dalam Pembuatan Rosario dan Pemasaran Digital - Chandra Dewi Kurnianingtyas; Parama Kartika Dewa; Josephine Sekar Gracella Tifanaputri (Jurnal Atma Inovasia, 2026)
Women’s empowerment initiatives represent a strategic effort to foster economic independence while simultaneously strengthening spiritual and social values within the community. One such approach is through training in the craft of rosary-making using cord and beads, which carries not only religious significance but also economic potential as a devotional handicraft product. This program is designed to enhance the skills of women, particularly within the Sang Timur community Semangkak Klaten, by enabling them to independently and creatively produce rosaries. As an innovation in community engagement, the training goes beyond the technical aspects of rosary production by incorporating education on digital marketing strategies. Participants are equipped with the skills to utilize social media platforms, online marketplaces, and product photography techniques to promote their creations more effectively and to a wider audience.